2016
DOI: 10.1007/s11356-016-6314-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxicopathic changes and genotoxic effects in liver of rat following exposure to diazinon

Abstract: In general, people may come in contact with mixtures of insecticides through domestic use, consumption of contaminated food or drinks, and/or living close to treated areas. We analyzed the toxic effects of diazinon on histological structure of liver and hematological parameters in male rats. DNA-damaging potential of diazinon was also investigated using the comet assay in blood cells and the micronucleus test in bone marrow. Two groups of six male rats orally received different amounts of diazinon: 1/50 and 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Tisch et al (2002) showed the potential carcinogenicity of DZN to human nasal mucosal cells. Toxicity effects of DZN on liver, kidney, and brain were also previously reported in animal models (Ezzi et al, 2016; Tsitsimpikou et al, 2013).…”
Section: Introductionsupporting
confidence: 64%
“…Tisch et al (2002) showed the potential carcinogenicity of DZN to human nasal mucosal cells. Toxicity effects of DZN on liver, kidney, and brain were also previously reported in animal models (Ezzi et al, 2016; Tsitsimpikou et al, 2013).…”
Section: Introductionsupporting
confidence: 64%
“…Cakici et al found that Diazinon produces vacuoles in the hepatocytes, increases Kupffer and inflammatory cells, and promotes congestion of the central veins in mice 9 . Ezzi et al in their research also proved that Diazinon distorts portal triads and congestion of central veins and sinusoids 16 .…”
Section: Discussionmentioning
confidence: 89%
“…22 Some antioxidant enzymes, like cytosol (SOD, PRDX, GPX) and peroxisomes (CAT), localize in separate cell compartments. 23 The mRNA levels of antioxidant enzymes GPX1, PRDX6, and SOD2 significantly increased in the DZN-exposed groups (Figure 2D), possibly serving as a protective mechanism which responds to the excessive ROS, accompanied by the increased mRNA and protein of CAT (Figure 7A). Transcriptome analysis with the aid of RNA-seq in the heatmaps of oxidative stress (Figure 2C) and ROS (Figure Collectively, the results supported that DZN exposure significantly induces oxidative stress in porcine granulosa cells.…”
Section: ■ Discussionmentioning
confidence: 97%